Transactions on Engineering Technologies World Congress on Engineering and Computer Science 2015 - Ao, Sio-Iong.; Kim, Haeng Kon.; Amouzegar, Mahyar A.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This proceedings volume contains selected revised and extended research articles written by researchers who participated in the World Congress on Engineering and Computer Science 2015, held in San Francisco, USA, 21-23 October 2015. Topics covered include engineering mathematics, electrical engineering, circuits, communications systems, computer science, chemical engineering, systems engineering, manufacturing engineering, and industrial applications. The book offers the reader an overview of the state of the art in engineering technologies, computer science, systems engineering and applications, and will serve as an excellent reference work for researchers and graduate students working in these fields.
Topics in engineering mathematics -- Topics in electrical engineering -- Topics in communications systems -- Topics in computer science -- Topics in chemical engineering -- Topics in systems engineering -- Topics in manufacture engineering -- Topics in industrial applications.
Keywords: Industrial engineering; Production engineering; Software engineering; Computer vision; Artificial intelligence; Industrial and Production Engineering; Software Engineering; Computer Vision; Artificial Intelligence